2021
DOI: 10.12688/f1000research.54361.1
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal antenatal care visits and newborn low birth weight in Bangladesh: a national representative survey

Abstract: Background: Low Birth Weight (LBW) is a global health concern for childhood mortality and morbidity. The objectives of this study were to assess the association between the number of Antenatal Care Visits (ANC) and LBW among Bangladeshi newborns, and to identify the demographic and socio-economic predictors of LBW.   Methods: Our present cross-sectional study is based on the secondary data of the Bangladesh Demography and Health Survey (BDHS) 2014. Complete data of 4,235 (weighted) mother-child pairs were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
5
2
Order By: Relevance
“…Unlike the findings of previous studies ( 42 , 44 ) , our findings did not show a significant association between being delivered from a short-stature mother as a determinant of stunting at birth. Similarly, there was a lack of significant association between stunting with not having ANC in the present study but reported in previous studies to have a significant association for children born from mothers who did not have ANC ( 13 , 45 , 46 ) . Possibly this might be due to the majority of mothers in the present study being multipara and they may get adequate nutrition information during their previous pregnancies.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Unlike the findings of previous studies ( 42 , 44 ) , our findings did not show a significant association between being delivered from a short-stature mother as a determinant of stunting at birth. Similarly, there was a lack of significant association between stunting with not having ANC in the present study but reported in previous studies to have a significant association for children born from mothers who did not have ANC ( 13 , 45 , 46 ) . Possibly this might be due to the majority of mothers in the present study being multipara and they may get adequate nutrition information during their previous pregnancies.…”
Section: Discussioncontrasting
confidence: 54%
“…The same survey reported the national prevalence of stunting, among under-five children as 37 % and out of which 17⋅1 % were below 6 months of age. Other studies noted that nearly half of the children were stunted in the Northwest, Southern and Eastern parts of Ethiopia (10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…21 In another study conducted in Bangladesh, it was revealed that mothers who received four or more antenatal care services had a 37% less possibility of having LBW babies compared to mothers who did not receive any antenatal care services or who received the services 1-3 times during the pregnancy. 22 Furthermore, this study observed mother's nutritional status have severe effect on the birthweight of newborns. Inadequate diet results in anemia and micronutrient deficiency during pregnancy have serious implications on the development of fetus.…”
Section: Discussionmentioning
confidence: 68%
“…), child (sex of child); and contextual (place of residence, region of residence) factors [2,4,5,[12][13][14][15][16][17][18][19][20][21]. Some previous studies in Bangladesh showed that maternal characteristics; child, and contextual factors were significantly associated with LBW [2,9,12,[22][23][24][25]. Additionally, a previous study conducted in Bangladesh identified that LBW was a significant factor in the likelihood of stunting and being underweight among underfive children [26,27].…”
Section: Introductionmentioning
confidence: 99%